Undergraduate curricular peer mentoring programs : perspectives on innovation by faculty, staff, and students - Smith, Tania, 1969- (Lexington Books, 2013)
Whether or not a college currently offers a Supplemental Instruction program, uses peer leaders in First-year Learning Community, or assigns Peer Tutors to courses, Undergraduate Peer Mentoring Programs will provide educators with concepts, examples, and findings useful for program development, innovation and enhancement. Contributors describe an international and interdisciplinary set of programs from the perspectives of program administrators, instructors, students.